2022
DOI: 10.3329/bjms.v21i1.56344
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Health-Related Quality of Life among Hepatitis C Patients in Pahang, Malaysia

Abstract: Background: Hepatitis C is one of the most common causes of liver disease worldwide. Health impacts of hepatitis C are not limited to physical morbidity but include psychosocial dimensions such as quality of life (QOL), depression, anxiety, and stigmatization. In Malaysia, modifiable factors that can improve QOL among hepatitis C patients have not been adequately studied. Resilience – defined as the capacity to endure hardships and rebound from life adversities – is associated with mental health and well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…The correlation between physical and mental state was confirmed in the studies of Zainulabid. 57 The results showed that patients with hepatitis C, but with higher rates of mental stability, were more likely to have a better quality of life compared to those who were less mentally stable. 57 Moreover, the research by Alan and Kurt 58 revealed the correlation between the level of anxiety and patients' perceptions of pain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The correlation between physical and mental state was confirmed in the studies of Zainulabid. 57 The results showed that patients with hepatitis C, but with higher rates of mental stability, were more likely to have a better quality of life compared to those who were less mentally stable. 57 Moreover, the research by Alan and Kurt 58 revealed the correlation between the level of anxiety and patients' perceptions of pain.…”
Section: Discussionmentioning
confidence: 97%
“…57 The results showed that patients with hepatitis C, but with higher rates of mental stability, were more likely to have a better quality of life compared to those who were less mentally stable. 57 Moreover, the research by Alan and Kurt 58 revealed the correlation between the level of anxiety and patients' perceptions of pain. Therefore, further study of this issue in different samples will contribute to the reduction of patients' anxiety.…”
Section: Discussionmentioning
confidence: 97%